The influence of budget planning, human resource competence, and budget implementation on budget absorption performance - Astuti, Eltin Yuli; Fadjarenie, Rien Agustin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to analyze the influence of budget planning, human resource competency, and budget implementation on budget absorption performance in the Special Criminal Offenses Prosecutor's Office. This type of research is mixed research, and the population in this study consists of the Finance Division employees in the Special Criminal Offenses Prosecutor's Office, totaling 65 employees. The sampling technique used in this study is the total sampling technique from the population members, known as a census or saturation sampling. Therefore, the sample size used in this study is all 65 employees of the population. The data collection technique used in this study is by distributing questionnaires to the 65 employees of the Finance Division in the Special Criminal Offenses Prosecutor's Office and conducting interviews with 5 employees consisting of the Commitment Maker Official (PPK), Head of Treasury Subdivision, Head of Accounting and Reporting Subdivision, Expenditure Treasurer (BP), and Assistant Expenditure Treasurer (BPP) as respondents to strengthen the research results. Data analysis technique using SmartPLS program version 3.0. The results of the study indicate that budget planning has a positive and significant effect on budget absorption performance. Human resource competency has a positive and significant effect on budget absorption performance. Therefore, the involvement of government officials with good competencies in their work will affect the resulting absorption. Budget implementation has a positive and significant effect on budget absorption performance, meaning that the better the budget implementation, the better the budget absorption performance.